Dampak Media Sosial terhadap Perilaku Belajar Siswa Di SDN 1 Banua Hanyar Kecamatan Pandawan - Ubaidillah (PT. Hasba Edukasi Mandiri, 2025)
This research is motivated by the development of social media, which is increasingly influencing the learning behavior of elementary school students, with both positive and negative impacts. While social media makes it easier for students to access learning information, it can also reduce concentration and discipline when used excessively. Therefore, this study aims to determine the impact of social media on student learning behavior at SDN 1 Banua Hanyar. This study employed field research with a qualitative approach. Data collection techniques included interviews, observation, and documentation. Interviews were conducted with the principal, teachers, students, and parents to obtain information regarding social media use and its impact on student learning behavior. Observations involved observing student learning activities at school, while documentation was used to supplement the research data, including photographs and other supporting documents. The data obtained were then analyzed descriptively and qualitatively. The results indicate that social media has both positive and negative impacts on student learning behavior. Positive impacts are evident in increased student access to learning materials, increased learning motivation, and improved learning communication. Meanwhile, negative impacts are evident in decreased concentration, lack of discipline, and reduced learning time due to excessive social media use. Therefore, supervision and guidance from teachers and parents are necessary to ensure that social media use provides greater benefits for students.